2009
DOI: 10.1021/cm9013392
|View full text |Cite
|
Sign up to set email alerts
|

Neodymium Dioxide Carbonate as a Sensing Layer for Chemoresistive CO2 Sensing

Abstract: We report the synthesis of neodymium hydroxide nanoparticles via a nonaqueous and surfactant-free sol−gel process and their subsequent thermal transformation into neodymium dioxide carbonate, which can be applied as a sensing layer for resistive-readout CO2 sensing. The sensors show an increase in resistance when exposed to CO2 in both dry and humid air in the operation temperature range of 250−400 °C, with a maximum sensor signal of 4 in humid air at 350 °C in 1000 ppm CO2. Another important feature of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 40 publications
1
84
0
Order By: Relevance
“…It can be seen that the relative gas response to 1500 ppm of CO 2 is about 2.2; that is, the measured current decreased from 2. [2][3][4][5]. It is especially notable in the case of recovery times, which have been found to be over 30 min in [2][3][4][5].…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…It can be seen that the relative gas response to 1500 ppm of CO 2 is about 2.2; that is, the measured current decreased from 2. [2][3][4][5]. It is especially notable in the case of recovery times, which have been found to be over 30 min in [2][3][4][5].…”
Section: Resultsmentioning
confidence: 93%
“…The measurements were made using the electrodes with 48 m gap width and 0.6 mm gap length. The current through the sample was monitored at the applied constant voltage of 3 V. Previously, it is reported that the sensor structures based on La and Nd oxycarbonate nanorods have high electrical resistivity and that restrict their use in commercial sensors [2][3][4]. In our sensor structures, the resistivity followed the Arrhenius law with an activation energy of 0.56 eV between 250 and 450 ∘ C. It shows that the conductivity is determined by deep trap levels, as the bandgap of the material, as concluded from X-ray absorption spectroscopy and X-ray emission spectroscopy studies by Hirsch et al [6], is approximately 3.7 eV in the case of La 2 O 2 CO 3 nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations